Створення та діяльність служби протоколу та зв'язку департаменту у справах генеральної асамблеї ООН і конференційному управлінню (1945-2025 рр.) (Серія: Історія. Політологія, 2025)
У дослідженні проаналізовано особливості створення та діяльності Служби протоколу та зв'язку Департаменту у справах Генеральної Асамблеї ООН і конференційному управлінню протягом 1945-2025 рр.Охарактеризовано еволюцію Служби, організаційні засади її функціонування, наведено повний перелік її керівників, розглянуто її сучасну структуру та персональний склад, розкрито розподіл обов’язків між співробітниками та вимоги до кандидатів на посади співробітників, а також визначено основні напрями діяльності Служби.Висвітлено зміст базового документа з питань протоколу – «Керівництва з протоколу», який застосовується у діяльності Служби та слугує орієнтиром для інших міжнародних організацій.Продемонстровано роль Служби у підготовці та підвищенні кваліфікації працівників протокольних служб системи ООН, дипломатичних представництв та міжнародних організацій. The article is devoted to the development of the Protocol and Liaison Service of the United Nations Department for General Assembly and Conference Management in the period 1945-2025.It is highlighted that protocol functions have been integrated into the structure of the UN Secretariat since the founding of the Organisation in 1945.The author analyses the stages of institutional formation of the Protocol and Liaison Service, its structural evolution, changes in functions and tasks in response to the growing scale and complexity of the UN activities.The author identifies the key organisational principles of the Service's functioning, including the principles of staff recruitment, division of responsibilities, and compliance with international protocol norms.The author provides a complete list of the heads of the Service, describes its current structure, staffing and distribution of responsibilities among employees.The main areas of activity are highlighted: organisation of official events, accreditation of delegations, protocol support of meetings and ceremonies, and advice on compliance with diplomatic norms.The article outlines the international legal documents regulating the activities of protocol services of international organisations.It is noted that the Protocol and Liaison Service is a key element of the UN organisational structure which ensures the effective functioning of the UN diplomatic mechanisms.The evolution of the Service reflects the general trends in the development of international protocol, strengthening of requirements for professionalism and compliance with ethical standards in the diplomatic sphere.The current activities of the Service are aimed at ensuring an adequate level of international communication, supporting multilateral dialogue and facilitating the effective work of the UN General Assembly and its departments.The further development of the Service will be determined by global challenges, the growing role of international organisations and the need to adapt to new formats of diplomatic interaction.Taking into account the historical experience is a prerequisite for the effective development, modernisation and improvement of the performance of the Protocol and Liaison Service and similar protocol services. This ensures not only stability and continuity, but also opens up opportunities for innovation, adaptation to new challenges and enhancing the role of the Service in the system of international relations.